The Integrative approach in transactional analysis as a theory and method in psychotherapy - Adam Bekier (Edukacyjna Analiza Transakcyjna)
The aim of this article is to analyze the integrative approach in transactional analysis (TA) as both a theory and method in psychotherapy. The contemporary integrative approach in TA expands traditional theoretical frameworks by incorporating elements from other schools of psychotherapy. This article discusses the core concepts of transactional analysis such as Ego states and life scripts within the integrative perspective, while also presenting specific to this approach concepts and methods in therapeutic practice. Particular attention is given to the dimensions of contact and relational dynamics within therapy.